Ipsilateral ectopic pregnancy in the distal remaining part of the previously removed Fallopian tube: a case report - Bassant Elshatby; Mohamed Mohamed Belal; Mohamed Emad Rezk (Journal of Medical Case Reports)
Abstract Background Ectopic pregnancy, occurring outside the uterine cavity, poses a significant health risk, with Fallopian tube involvement being predominant. Recurrent ectopic pregnancy, particularly in the ipsilateral remnant of a previously removed tube, is a rare and poorly understood phenomenon. Here, we present a case of recurrent ectopic pregnancy occurring in the distal remnant of the right fallopian tube following ipsilateral incomplete salpingectomy in a 22-year-old woman. Case presentation A 22-year-old woman of mixed Arab ancestry and African ethnicity, gravida 4, para 1, with a history of one miscarriage and a previous ectopic pregnancy, presented to Elshatby Maternity Hospital, Alexandria, Egypt, complaining of severe lower abdominal pain with a history of an open right salpingectomy one year prior due to the ectopic pregnancy. She exhibited stable vital signs on admission. Ultrasound revealed a 6-week gestational sac in the right fallopian tube, accompanied by hematoma and mild pelvic collection. Despite analgesic interventions, her symptoms worsened the next day, prompting open surgery. Surprisingly, the distal portion of the right tube, which was supposed to have been removed in the prior salpingectomy, contained the ectopic pregnancy. A laparotomy was performed, involving evacuation of the pelvic hematoma, distal ipsilateral tubal salpingectomy, and peritoneal lavage. Postoperative recovery was uneventful, with improvement demonstrated during follow-up. Conclusion Caution should be taken when dealing with any woman in the reproductive age group who presents with acute abdomen, especially if she has a previous history of ectopic pregnancy, to exclude the possibility of recurrent ectopic pregnancy. Previous salpingectomy does not exclude the possibility of recurrent ectopic pregnancy on the ipsilateral side, as the inappropriate surgical technique used during salpingectomy can affect the possibility of recurrence. We suggest that careful clinical consideration of the surgical technique used during salpingectomy is essential to minimize the risk of recurrent ectopic pregnancies and prevent serious complications.